Classification of the Indian Arid Zone: Bioclimatic and Phytogeographic Approaches - Meher-Homji, V M (Annals of Arid Zone, 2016)
An attempt has been made to demarcate the arid and the semiarid zones of India using bioclimatic and vegetational criteria. An index of aridity-humidity based on the values of precipitation and length of dry season seems to delineate the dry zones fairly well with varying degrees of aridity Another approach is to apply the climatic formulae of several authors to a station for a large number of individual years. A truly arid station is one turning out arid according to all the formulae, all the years. Vegetation types a)so help in characterising the degrees of aridity; we have in decreasing order of aridity, the Calligonum type of the desert sand-dunes. Prosopis-Capparis-Ziziphus-Salvadora of western Rajasthan, Acacia-Capparis decidua of northern Gujarat and the Deccan, and Acacia senegal-Anogeissus pendula and A. catechu-A. pendula of the Aravallis. The climo-vegetational history has also been reviewed.